Editorial: Prizing Equity in Education and Research in the Field of Open, Flexible and Distance Learning - Niki Davis; Alison Fields; Maggie Hartnett (Flexible Learning Association of New Zealand, 2014)
Valuing more open and equitable approaches to practice and research in the field of flexible, open, and distance learning enables the editors of the Journal of Open, Flexible and Distance Learning (JOFDL) to better describe the distinctive mission for the journal, which is uniquely situated in a bicultural nation where complementary approaches of indigenous cultures and western science are best braided. Three of the four research papers introduced for this issue provide answers to the DEANZ 2014 conference question of "Where is the 'e' in engagement?", which referred to engagement of students from organisational and faculty perspectives. Bonk and Khoo's (2014) recent text book on that conference topic is also celebrated in a book review. In contrast, the fourth paper identifies the possibilities for increased engagement between administrators and the staff that they lead in virtual charter schools. The editorial also describes the increasing visibility of JOFDL in collections worldwide.